2019 IEEE Symposium on Security and Privacy (SP) 2019
DOI: 10.1109/sp.2019.00059
|View full text |Cite
|
Sign up to set email alerts
|

"Should I Worry?" A Cross-Cultural Examination of Account Security Incident Response

Abstract: Digital security technology is able to identify and prevent many threats to users accounts. However, some threats remain that, to provide reliable security, require human intervention: e.g., through users paying attention to warning messages or completing secondary authentication procedures. While prior work has broadly explored people's mental models of digital security threats, we know little about users' precise, in-themoment response process to in-the-wild threats. In this work, we conduct a series of qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Although other works [14,19,26] have been equally critical of these aforementioned mitigations, research also shows that privacy and security solutions must be targeted [15,21,33,36,42]. As such, this exercise raised several questions that can help guide future work on technology abuse in IPV scenarios:…”
Section: Discussion and Research Questionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although other works [14,19,26] have been equally critical of these aforementioned mitigations, research also shows that privacy and security solutions must be targeted [15,21,33,36,42]. As such, this exercise raised several questions that can help guide future work on technology abuse in IPV scenarios:…”
Section: Discussion and Research Questionsmentioning
confidence: 97%
“…As such, this exercise is then used to present several relevant research questions that may help guide future works on online privacy protection of IPV victims in a targeted fashion, considering culture and the reality in which they are immersed. Our goal is to join the chorus of researchers [21,33,36] positing that one-size-fits-all solutions might not be effective and need to consider the reality of specific vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%
“…When advised or required to change their passwords by the notification, less than a third of respondents reported any intention to change their passwords [35]. Other recent work has shown that when a security incident occurs that involves accounts on a major social network, people exhibit a variety of responses, from doing nothing to actively seeking out information [69].…”
Section: Awareness and Perceptions Of Security Incidentsmentioning
confidence: 99%
“…A study about breaches and consumers found that customers' spend-ing at a retailer fell significantly after the retailer suffered a breach [24], while another survey found that only a minority of respondents would stop doing business with a company after a breach [7]. Other work has found that people react to security incidents involving accounts on a major social network in a variety of ways, from doing nothing to actively seeking out information [37].…”
Section: Data Breaches and Security Incidentsmentioning
confidence: 99%